2019
DOI: 10.1051/0004-6361/201834955
|View full text |Cite
|
Sign up to set email alerts
|

LQAC-5: The fifth release of the Large Quasar Astrometric Catalogue

Abstract: Context. In addition to their great astrophysical interest, quasars represent quasi-ideal reference objects in the celestial sphere with, a priori, a lack of significant proper motion. Since the fourth release of the Large Quasar Astrometric Catalogue (LQAC-4), a large number of quasars have been discovered, in particular those coming from the DR14Q release of the SDSS. With the advent of the Gaia Data Release 2 (DR2), it is now also possible to fold in extremely accurate quasar positions. Aims. Following the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…In this paper we have constructed an improved version of the LQAC5 catalogue (Souchay et al 2019), which we called LQAC5+, by matching its total sample of 592809 quasars with the Gaia EDR3 catalogue (Brown et al 2018) This process, with a search radius of 1", led to 416113 cross-matched objects, which correspond to 70.2 % of the totality. A lack of crossmatches in the vast majority involve objects too faint to be detected by the satellite, whose magnitude threshold is G = 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we have constructed an improved version of the LQAC5 catalogue (Souchay et al 2019), which we called LQAC5+, by matching its total sample of 592809 quasars with the Gaia EDR3 catalogue (Brown et al 2018) This process, with a search radius of 1", led to 416113 cross-matched objects, which correspond to 70.2 % of the totality. A lack of crossmatches in the vast majority involve objects too faint to be detected by the satellite, whose magnitude threshold is G = 21.…”
Section: Discussionmentioning
confidence: 99%
“…In the mean time, Souchay et al (2019) constructed an updated version of the Large Quasar Astrometric Catalogue (LQAC; Souchay et al 2009), LQAC-5, which consists of a compilation of all the objects duly identified as quasars by the authors of the catalogues belonging to the compilation, with criteria adapted to the different properties of the surveys involved and their observational capabilities. Readers should notice that the LQAC-5 does not consist of a mere compilation of catalogues of quasars, but it contains useful additional data such as the optimized determination of the equatorial coordinates of the objects not detected by Gaia, mainly through the Large Quasar Reference Frame LQRF (Andrei et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There have been various efforts to identify extragalactic objects in the Gaia releases, mostly via a positional cross-match to other catalogues. Souchay et al (2019), for example, cross-matched the Sloan Digital Sky Survey (SDSS) Data Release 14 quasar catalogue to GDR2, finding 399 000 counterparts within 1 in the latter. Liao et al (2019) compiled a list of 1.8 million quasars from various sources, about one million of which match to GDR2 objects to within 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We were also curious about a possible dependence of the offset with redshift, as suggested in Zacharias & Zacharias (2014); Makarov et al (2017). In order to check this effect, we included in our analyses the redshift z taken from the the fifth release of the Large Quasar Astrometric Catalogue (LQAC-5; Souchay et al 2019).…”
Section: Methodsmentioning
confidence: 99%